2018
DOI: 10.1051/matecconf/201820405003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and physical properties of aluminium-silicon (Al-Si) casting alloys reinforced by Zinc Oxide (ZnO)

Abstract: This study aimed to enhance the properties of aluminiumsilicon (Al-Si) alloys by adding zinc oxide as a reinforcing material. This study was a type of pre-experimental design called the one-shot case study, in which sample groups subjects were given treatments and then observed. The steps included melting the aluminium-silicon in a furnace at 900° C, adding a certain amount of zinc oxide (0.05%, 0.1%, or 0.2%), stirring the mixture for 1 minute, and pouring it into a permanent mould. Results showed that, among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Aluminum alloys are commonly used in the automotive and aerospace industries due to their favorable properties, such as a high strength-to-weight ratio, ease of fabrication, good thermal conductivity, and good corrosion resistance [1][2][3][4]. Among these alloys, aluminum-silicon alloys are commonly used to manufacture combustion engine components, such as pistons and cylinder heads, which typically operate at elevated temperatures [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum alloys are commonly used in the automotive and aerospace industries due to their favorable properties, such as a high strength-to-weight ratio, ease of fabrication, good thermal conductivity, and good corrosion resistance [1][2][3][4]. Among these alloys, aluminum-silicon alloys are commonly used to manufacture combustion engine components, such as pistons and cylinder heads, which typically operate at elevated temperatures [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…During the experimental investigation, the temperature and total strain of the material are kept constant while the stress gradually decreases over time. Under the action of time, the elastic strain inside the material gradually transforms into the process of plastic strain [4]. During the relaxation test, stress reduction is measured as a function of time.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminium matrix composites (AMCs) have been developed by various processing techniques. Among these routes, stir casting is the proved auspicious techniques for producing AMCs because of their easiness, suppleness, inexpensive and appropriate to large quantity fabrication [14,15]. Poppy Puspitasari et al [16] studied the mechanical properties in Al-Si alloy with the presence of ZnO particles and reported that by adding ZnO, the strength and hardness of the composite have been improved.…”
Section: Introductionmentioning
confidence: 99%